Geometric Parameter Control for Tunable Resonance Frequencies in Asymmetric Nanodots: Equilibrium States and Dynamic Response - Escrig-Murua, J; Saavedra-Díaz, E (Institute of Physics, 2024)
Through numerical simulations, we delve into the examination of the equilibrium state and dynamic response of asymmetric nanodots. Within these nanodots, we identify two distinct equilibrium states—single domain and vortex. Our findings reveal a direct correlation between the number and frequencies of peaks and the minimum energy configuration, which is contingent upon the physical parameters of the system. This observation implies the potential to intentionally manipulate a desired set of frequencies by precisely controlling the geometric parameters of the system. © 2024 IOP Publishing Ltd. All rights, including for text and data mining, AI training, and similar technologies, are reserved.